High-performance Microwave Computational Imaging System Based on Information Metamaterials - Jiaqi HAN; Shuncheng TIAN; Hao YI; Xiangjin MA; Guisheng LIAO; Long LI (Leida xuebao, 2021)
In this paper, we propose a detailed architectural design, principle of operation, and modeling analysis of a high-performance microwave computational imaging system based on information metamaterials. We use the excellent electromagnetic wave manipulation capabilities of information metamaterials, combined with compressive sampling theory, and elaborate the design approaches of stray beam generation and high-performance radiation. Furthermore, we develop a numeric model for describing this imaging system and propose a high-performance frequency-diverse information metamaterial element whose band stop characteristic can cover the X-band. Based on the element, a high-performance information metamaterial lens is designed, which achieved 75% radiation efficiency, which is three times compared with existing metamaterial apertures over the imaging region. Finally, on the basis of the proposed numeric model, we compute and reconstruct ideal scattering objects using the high-performance information metamaterial lens, validating the ability of image restoration. Study on the high-performance microwave computation imaging system in this work laid the foundation for solid theory and prospective exploration, which can be applied for imaging radar, security monitoring, and medical testing.